PEMBUATAN INFUSED WATER DAUN KAYU MANIS BALI (DAUN KATUK) DAN PEMANFAATANNYA BAGI KESEHATAN - Ni Made Sukma Sanjiwani; Ni Putu Ayu Mirah Mariati; Agung Ari Chandra Wibawa; I Wayan Surya Rahadi; Dewa Ayu Ika Pramitha; I Wayan Sudiarsa (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2023)
Banjar abasan is one of the banjars in Singapadu village, Sukawati sub-district, Gianyar regency, Bali province, Indonesia, precisely located to the south of banjar kutri and to the north of banjar kebon. Cinnamon plants grow a lot in the homes of banjar abasan residents and most of the residents of banjar abasan do have cinnamon plants in their homes. The purpose of making cinnamon leaf infused water is to produce young men and women of banjar abasan to be able to make cinnamon leaf infused water which in the future can be used as a business or sold by young men and women of banjar abasan because seen from the potential of young men and women of banjar abasan who have the potential to be able to make cinnamon leaf infused water because cinnamon leaf infused water is very beneficial for health. In this service, assistance is provided to the banjar abasan community, especially young people and youths so that they can make and analyze the pH of cinnamon leaf infused water. Socialization and demonstration will be carried out in month 5 which begins with giving a pre-test, then a socialization session, a demonstration session for making cinnamon leaf infused water and testing the pH of cinnamon leaf infused water and ends with giving a post-test in order to hone community knowledge about this community service. This service is very beneficial for the abasan community because they are given knowledge related to cinnamon leaf infused water, the abasan community also gets knowledge on how to make cinnamon leaf infused water and pH testing of cinnamon leaf infused water, with the knowledge given, the abasan community knows and can make infused water independently with the assistance, socialization and demonstration program. The mandatory outputs that have been achieved in this research are: Video of activities on Youtube, news writing in print/electronic media, final report and learning integration.